2016
DOI: 10.1080/09585192.2015.1109538
|View full text |Cite
|
Sign up to set email alerts
|

Performance appraisals and job satisfaction

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(130 citation statements)
references
References 92 publications
(78 reference statements)
8
113
0
9
Order By: Relevance
“…On the other hand this can also mean that, HRM practices probably may have indirect influence on employee turnover intentions, while job satisfaction may directly impact employee turnover intentions. This seconds the results revealed by [33] [53] [56] who evidenced job satisfaction as mediator between specific HRM practices and turnover intentions.…”
Section: Path Analysissupporting
confidence: 85%
See 2 more Smart Citations
“…On the other hand this can also mean that, HRM practices probably may have indirect influence on employee turnover intentions, while job satisfaction may directly impact employee turnover intentions. This seconds the results revealed by [33] [53] [56] who evidenced job satisfaction as mediator between specific HRM practices and turnover intentions.…”
Section: Path Analysissupporting
confidence: 85%
“…Researchers found that job satisfaction plays an intermediary role between internal service quality and organizational performance; time stress and health outcomes and core self-evaluation and burnout [53]. In the analysis of turnover intention, researchers also found the role of job satisfaction as an intermediary ( [33]; [54]). Job satisfaction mediates the influence of salary and promotion on turnover intention [55].…”
Section: Job Satisfaction As a Mediatormentioning
confidence: 99%
See 1 more Smart Citation
“…The results of Bakotić (2016) showed that there is a direct relationship between employee job satisfaction and organizational performance in both directions, but the intensity of the relationship is very weak. Also, Kampkötter (2017) found that financial rewards have a significant effect on employee performance. (Yuen et al, 2018) also showed that job satisfaction was significantly related to job performance.…”
Section: Employee Performancementioning
confidence: 99%
“…5 Fourth, performance appraisals give employees direct feedback about their performance and potential strengths and weaknesses. Feedback can show employees whether to reallocate efforts or to invest in new skills and, moreover, can have a direct impact on employee satisfaction and thus the decision to stay with an employer (Fletcher and Williams, 1996;Whitman et al, 2010;Kampkötter, 2015).…”
Section: Purposesmentioning
confidence: 99%